User Perception-Based Optimal Route Selection for Vehicles of Disabled Persons in Urban Centers of Saudi Arabia - Fawaz Alharbi; Abdulmajeed Alshammari; Meshal Almoshaogeh; Arshad Jamal; Husnain Haider (Applied Sciences)
People with disabilities (PWD), in their routine commutes, confront hindrances associated with road infrastructure in busy urban centers. The present study developed a user perception-based methodology to evaluate optimal routes for PWD in urban settlements in the Kingdom of Saudi Arabia (KSA). A survey captured the preferences for 105 PWD, consisting of 37 powered wheelchair users, 62 manual wheelchair users, and 6 artificial limb users. The multi-criteria decision analysis evaluated the accessibility index for PWD based on four criteria: length, number of junctions, absence of footpath, and slope. This study revealed that manual wheelchair users prefer the length criterion, powered wheelchair users emphasized the absence of footpaths, and artificial limb users were concerned about slope. The result showed that only two routes out of ten showed medium, while those remaining exhibited low accessibility. Most routes were relatively long for people with disabilities, focusing on the need for public transportation with special arrangements in most small and medium-sized cities, like the study area of Hail and Qassim province of the KSA, to reduce the distance and travel time. The proposed framework provides valuable insights to route evaluation for persons with special needs in the KSA and elsewhere.